2018
DOI: 10.3390/ma11040535
|View full text |Cite
|
Sign up to set email alerts
|

The Design of 3D-Printed Lattice-Reinforced Thickness-Varying Shell Molds for Castings

Abstract: 3D printing technologies have been used gradually for the fabrication of sand molds and cores for castings, even though these molds and cores are dense structures. In this paper, a generation method for lattice-reinforced thickness-varying shell molds is proposed and presented. The first step is the discretization of the STL (Stereo Lithography) model of a casting into finite difference meshes. After this, a shell is formed by surrounding the casting with varying thickness, which is roughly proportional to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In a study by Shangguan et al [ 18 ], they fabricated molds with a shell-truss structure using 3D printing, reducing the use of materials by two-thirds compared to conventionally-made molds. In addition, the cooling time of melting aluminum could be successfully controlled by the application of lightweight structures [ 19 ]. Deng et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Shangguan et al [ 18 ], they fabricated molds with a shell-truss structure using 3D printing, reducing the use of materials by two-thirds compared to conventionally-made molds. In addition, the cooling time of melting aluminum could be successfully controlled by the application of lightweight structures [ 19 ]. Deng et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behavior of the skeletal sand mold is very important in the thermomechanical coupled modeling and simulation. Its strength, measured by Shangguan et al [21], declines significantly with temperature, as shown in Figure 3. Usually, the sand mold is neglected or treated as an elastic model.…”
Section: Treatment Of Sand Moldmentioning
confidence: 79%
“…The available research studies have been focused on the influence of the following process parameters (Hodder and Chalaturnyk, 2019): analysis of the cast dimensional accuracy pouring aluminum alloys (Le Néel et al , 2018b); measuring the influence of the part/wall thickness on the part cooling time (Walker et al , 2018); leverages binder jetting technology to design a smart molds with sensor integrated to study the thermodynamics and physics of the casting process (Szymański and Borowiak, 2019); testing the effect of different sand graininess and different binder on the casted part roughness. Furthermore, several studies have been conducted on the generation of complex molds via the use of 3D printing: cellular structures have been designed to obtain complex aluminum (Snelling et al , 2015; Kim et al , 2018) and iron casts (Wang et al , 2019; Druschitz et al , 2017) or lattice-reinforced thickness-varying shell molds (Shangguan et al , 2018; Shangguan et al , 2017).…”
Section: Introductionmentioning
confidence: 99%